From biomolecules to breakthroughs: exosomes as next-generation theranostics in female infertility - Aldarmahi, Ahmed A.; Khanday, Shifan; Taher, Ehab S.; Abdeen, Ahmed; Atia, Gamal A.; Mohammed, Dania A.; Nasr, Dina S.; Albarakati, Rayan G.; Zaghamir, Donia E.; Hetta, Helal F.; Atwa, Ahmed M.; Abass, Kasim S.; et al. (Frontiers in Cell and Developmental Biology, 2025)
Female infertility and reproductive disorders represent a significant global health challenge, with complex etiologies often linked to impaired cellular communication, inflammation, and tissue dysfunction. Exosomes (EXOs), nanosized extracellular vesicles laden with bioactive molecules, have become recognized as significant transmitters of intercellular signaling in reproductive physiology and pathology. This review comprehensively discusses the dual diagnostic and therapeutic potential of EXOs in addressing female infertility disorders, such as endometriosis, polycystic ovary syndrome (PCOS), primary ovarian insufficiency (POI), Asherman syndrome, and gynecological cancers. We investigate the strategies whereby EXOs govern important activities like endometrial regeneration, folliculogenesis, immune modulation, and angiogenesis, while highlighting their role in restoring ovarian and uterine homeostasis. Advances in exosome isolation techniques, bioengineering strategies (e.g., cargo loading, surface modification), and scaffold-based delivery systems are critically evaluated for their capacity to enhance therapeutic precision and efficacy. Notwithstanding their potential, issues include standardization of isolation protocols, scalability, and long-term safety, which necessitate further research. By integrating molecular insights with translational innovations, this review underscores the clinical implementation of exosome-based therapeutics in revolutionizing reproductive medicine, offering new hope for personalized, non-invasive treatments in female fertility restoration.